Medieval Healthcare and the Rise of Charitable Institutions - Ziegler, Tiffany A. author. aut Link
VI, 155 p.
Keywords: Medieval Healthcare and the Rise of Charitable Institutions: The History of the Municipal Hospital examines the development of medieval institutions of care, beginning with a survey of the earliest known hospitals in ancient times to the classical period, to the early Middle Ages, and finally to the explosion of hospitals in the twelfth and thirteenth centuries. For Western Christian medieval societies, institutional charity was a necessity set forth by the religion’s dictums—care for the needy and sick was a tenant of the faith, leading to a unique partnership between Christianity and institutional care that would expand into the fledging hospitals of the early Modern period. In this study, the hospital of Saint John in Brussels serves as an example of the developments. The institution followed the pattern of the establishment of medieval charitable institutions in the high Middle Ages, but diverged to become an archetype for later Christian hospitals. .